Analysis of the Design and Feasibility of Volta Drive Connect as a Renewable Energy-Based Science Media to Strengthen the Pancasila Students’ Profile - Khaerini Rahmania; Nasokah Nasokah; Ashief El Qorny (Jurnal Pijar MIPA, 2026)
Science learning on renewable energy concepts in elementary schools today is often theoretical, conventional, and lacks contextual hands-on experience for students. This study aims to comprehensively describe the physical design characteristics of a renewable energy-based science learning media called Volta Drive Connect, analyze its technical and instructional feasibility level, and explore its potential in depth in strengthening the dimensions of the Pancasila Student Profile (PPP). The method used in this study is a mixed-methods approach with a convergent parallel design, in which data are collected simultaneously through passive participatory observation of classroom learning dynamics, semi-structured interviews with teachers and grade IV students at Kakuka National Elementary School, and documentation of artefacts of student learning outcomes in the field. The results of the study showed that the Volta Drive Connect science media met the excellent eligibility criteria for children's work safety, ease of operation, clarity of visual guide instructions, and educational practical value in the classroom, with an average expert-rated validity of 92%. This solar vehicle science teaching kit is designed adaptively, which is divided into three levels of mechanical complexity (Beginner, Intermediate and Advanced) and utilizes local inorganic recycled materials as the main chassis component. From the pedagogical side of the Independent Curriculum, the use of concrete media is actually able to actualize the dimensions of the Pancasila Student Profile holistically. The actualization includes the dimensions of 'Faith and Fear of God Almighty, and Noble Character' which is stimulated through the growth of ecological awareness, the dimensions of 'Critical Reasoning' and 'Creative' which are honed through solar energy conversion experiments and mechanical troubleshooting activities independently, as well as the dimension of 'Gotong Royong' which is formed from collaboration in solving technical problems in groups.